Strategy to Increase the Operational Cost Efficiency of Water Treatment Plants by Integrating Green Concept and Value Engineering - Hendy Gunawan Putra; Budi Susetyo (Green Publisher Indonesia, 2026)
The government prioritizes achieving 100% access to drinking water under Vision 2030, with a service coverage target of 94.61% in Tangerang Regency by 2030. Water Treatment Plants (WTPs) are a crucial component of clean water supply systems; however, their operations can pose environmental impacts. This research analyzes the operational cost efficiency of WTPs by integrating green concepts with the Value Engineering (VE) method. The study aims to identify economical and environmentally friendly solutions without compromising water quality and quantity by pinpointing key factors that influence operational cost efficiency. The methodology includes a literature review, hypothesis formulation, and data collection through questionnaires, analyzed using Structural Equation Modeling (SEM) and VE studies. Results indicate that sustainable technology with renewable energy use and innovation implementation are the most influential variables. A case study at PERUMDAM TKR WTP applies VE and Life Cycle Cost Analysis (LCCA) to assess operational cost efficiency under a green concept. The VE results show an 8.97% cost increase amounting to IDR 1,717,378,957, while LCCA findings demonstrate that green concept investments in WTPs are financially feasible, with NPV > 0 (IDR 14,076,121,227.33), an IRR of 16.42%, and a payback period of 8.60 years.